Activating impurity effect in edge nitrogen-doped chevron graphene nanoribbons. (19th April 2018) - Lv, Yawei; Huang, Qijun; Chang, Sheng; Wang, Hao; He, Jin; Liu, Anqi; Ye, Shizhuo; Wang, Wei
Abstract: Doping has been regarded as one of the most important band structure engineering methods for graphene and its derivatives. Here, we theoretically investigate the chevron-type graphene nanoribbon (CGNR) which is doped by nitrogen in its edges (N-CGNR). The impurity effect can be activated by hydrogen efficiently. When each N atom is adsorbed by a H atom, the σ bond of N induced by self-hybridization is replaced by the N-H sp 2 bond, leaving two p z electrons perpendicular to the CGNR plane. Only one p z electron can be bonded with the nearest C atom. Therefore, the residual p z electron is delocalized from the N atom and induces the n -type impurity effect. We have calculated the binding energies of N-H bonds and found they are stable and can be manipulated independently without impacting the other bonds. A molecular dynamic (MD) simulation under high temperature further verifies that the N-H bonds in some specific positions can even be stable at 2000 K. Finally, the activated impurity effect is exhibited in the transport properties of CGNR based devices, indicating its wide application prospects.